Discovering Cathodic Biocompatibility for Aqueous Zn–MnO2 Battery: An Integrating Biomass Carbon Strategy - Lv, Wei; Shen, Zilei; Li, Xudong; Meng, Jingwen; Yang, Weijie; Ding, Fang; Ju, Xing; Ye, Feng; Li, Yiming; Lyu, Xuefeng; Wang, Miaomiao; Tian, Yonglan; et al. (Nano-Micro Letters, 2024)
Developing high-performance aqueous Zn-ion batteries from sustainable biomass becomes increasingly vital for large-scale energy storage in the foreseeable future. Therefore, γ-MnO2 uniformly loaded on N-doped carbon derived from grapefruit peel is successfully fabricated in this work, and particularly the composite cathode with carbon carrier quality percentage of 20 wt% delivers the specific capacity of 391.2 mAh g−1 at 0.1 A g−1, outstanding cyclic stability of 92.17% after 3000 cycles at 5 A g−1, and remarkable energy density of 553.12 Wh kg−1 together with superior coulombic efficiency of 100%. Additionally, the cathodic biosafety is further explored specifically through in vitro cell toxicity experiments, which verifies its tremendous potential in the application of clinical medicine. Besides, Zinc ion energy storage mechanism of the cathode is mainly discussed from the aspects of Jahn–Teller effect and Mn domains distribution combined with theoretical analysis and experimental data. Thus, a novel perspective of the conversion from biomass waste to biocompatible Mn-based cathode is successfully developed. Highlights: 1 γ-MnO2 loaded on N-doped biomass carbon from grapefruit peel is firstly developed. 2 The splendid cathodic properties (e.g., coulombic efficiency: 100%, energy density: 553.12 Wh kg−1) are gained. 3 The biomass strategy guaranteed via cytotoxicity test shows a clinical potential. 4 Zn-ion storage efficiency is boosted mainly by regulating Mn–O bond and Mn domains.